2021
DOI: 10.4081/ecj.2021.9570
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with emergency department length of stay of internal medicine patients

Abstract: Emergency Department (ED) Length Of Stay (ED-LOS) is associated with quality of care, patient safety and treatment outcome. The aim of this study is to identify factors associated with ED-LOS of internal medicine patients and provide recommendations to shorten ED-LOS. A retrospective cohort study was conducted in a single center in the Netherlands. Anonymised data of 7,380 ED attendances from January 2016 to January 2018 were analyzed. Data included time of ED arrival and departure, sex, age, source of referra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In the current study, 42.25% (95% CI: 37.5%−47.0%) of patients stay longer than 24 h in the ED. According to the Ethiopian Hospital Service Transformation Guidelines, 13 the LOS in the ED should not be prolonged for more than 24 h, The current finding shows the proportion of patients who stayed longer than the recommended hours is higher than the result of the study conducted in the Netherlands, 14 Switzerland, France, and the United States. The variation could be attributed to differences in sample size and quality of healthcare services.…”
Section: Discussionmentioning
confidence: 48%
See 4 more Smart Citations
“…In the current study, 42.25% (95% CI: 37.5%−47.0%) of patients stay longer than 24 h in the ED. According to the Ethiopian Hospital Service Transformation Guidelines, 13 the LOS in the ED should not be prolonged for more than 24 h, The current finding shows the proportion of patients who stayed longer than the recommended hours is higher than the result of the study conducted in the Netherlands, 14 Switzerland, France, and the United States. The variation could be attributed to differences in sample size and quality of healthcare services.…”
Section: Discussionmentioning
confidence: 48%
“…Similarly, the previously conducted studies identified the association of the triage type with the LOS in ED but with different description and number of triage categories. 14,19,20 Moreover, the diagnostic investigation was significantly associated with the LOS. Patients without laboratory and radiological evaluations spend less time in an ED compared to their counterparts.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations